(untitled) (Indian Journal of Traditional Knowledge (IJTK), 2023)
In the Vedic literature, one can see the mention of silver, ’Rajatam’, for diversified day-to-day applications to lead a healthy life. The paper reports the scientific validation of traditional knowledge of synthesising chemical-free, stable metal nanoparticles (NPs), taking silver as an example. Here, silver nanoparticles (SNPs) are synthesised with the assistance of convection current in the water. The prolonged heating of double-distilled water in a silver vessel enables to get a colloidal solution of SNPs. The SNPs produced are characterised by UV-Visible absorption spectroscopy, Field-emission Scanning Electron Microscopy, High-resolution Transmission Electron Microscopy, and Energy Dispersive X-Ray Spectroscopy. Stability of SNPs is revealed through ageing studies with glucose as the surfactant. The method could synthesise stable SNPs of size 30-40 nm. This accounts for the possible reason for taking silver as the material for utensils for cooking food by the ancient Indians, Greek, Romans, Persians and Egyptians.